The black rice ethanol extract effect on polymorphonuclear cells proliferation of rats induced by lipopolysaccharide - Henny Juliastuti; Maman Djamaludin; Hadi Alwani (ACTA Medical Health Sciences, 2022)
Inflammation is a natural defense response of the body when an infection occurs. However, excessive inflammatory reactions can be triggered by lipopolysaccharides (LPS), which are key immunogenic components of bacterial capsules or cell walls. These reactions can lead to harmful effects on the body. Black rice (Oryza sativa L. indica) is a natural source rich in phenols, flavonoids, and antioxidant anthocyanins, which act as immunomodulators. This study aimed to investigate the effect of black rice ethanol extract as an anti-inflammatory agent on the proliferation of polymorphonuclear cells (PMN) in the spleen of rats induced by lipopolysaccharides. The study involved 27 mice, which were given a 400 mg/kg BW dose of black rice ethanol extract for 14 days. Afterward, the rats were induced with 0.3 mg/kg BW LPS intraperitoneally 24 hours before euthanasia using CO2. The spleens were then collected to measure the size of the germinal center diameter. The results showed that the treatment group had a germinal center diameter of 1.311 ± 0.226 μm (p<0.05) when compared to the positive control group. The LPS administration in the control group resulted in the disorganization of the white pulp and a reduction in lymphocyte cells and PMN in the germinal center. In conclusion, black rice ethanol extract at a dose of 400 mg/kg BW has an effect on PMN proliferation, as indicated by changes in the morphology of the white pulp in the germinal center of the spleen in rats. DOI : 10.35990/amhs.v1n1.p38-44 REFERENCES Wahyuningsih P, UP Nursing. Effect of Tintir Distance Extract (Jathropa Multifida Linn) on the Amount of PMN and Mast Cells on Rat Wound Healing with Acute Need Model. Journal Homepage. 2019;4(1):1-6. Harlim A. Textbook on Skin Health Science and Genital Immunology. Henny Juliastuti, et.al. Inflammatory. 2008. FK UKI; p. 1386. VK's sgiaman. Improved Wound Healing in the Oral Mucosa Through the Administration of Aloe Vera (Linn.) Topically. Maranatha Journal of Medicine and Health. 2011;11(1):70-79. Hannoodee S, Dn N. Acute Inflammatory Response: Issues of Concern and Clinicopathologic Correlations. Acute Inflammatory Response. Published online 2021:7-10. FK Treasure. Evaluation of Phytochemicals, Antioxidant Activity, and Immunomodulators of Black Rice (Oryza Sativa L. Indica). 2016. Wijayanti CRT. Anti-Inflammatory Power of Ethanolic Extract of Tripterygium Rootwilfordii Hook. F. on Female White Squeak. Thesis, Sanata Dharma University. Published online 2008:12-13. Alviyani E. Test the Antioxidant Activity of White Rice Ethanol Extract and Black Rice Using the DPPH Method in Gel Form. Thesis. Published online 2020:1-120. FK Treasure. Anti-inflammatory Activity of Ethanol Extract and Black Rice Water (Oryza Sativa L. Indica) in Male Wistar Rats. Journal of Recapangan. 2016;10(1):9-15. Liu H, Huang L, Pei X. Effects of Sorghum Rice and Black Rice on Genes Associated with Cholesterol Metabolism in Hypercholesterolemic Mice Liver and Intestine. Food Science and Nutrition. 2021;9(1):217-229. Bronte V, Pittet MJ. The Spleen in Local and Systemic Regulation of Immunity. Immunity. 2013;39(5):806-818. Noor Mutsaqof AA, -W, Suryani E. Expert System for Diagnosing Infectious Diseases Using Forward Chaining. ITSmart Journal of Technology & Information. 2016;4(1):43. Abidin Z. Effects of Ethanol Extract of Oryza Sativa L. Indica on Kinase B Protein Activity and Serum CA 15-3 Levels in Female Dawley Sprague Mice. eJournal Medis Indonesia. 2017;4(3):187-190. Mangiri J, Mayulu N, Kawengian SES. An Overview of the Nutritional Content in Black Rice Cultivar Pare Ambon South Sulawesi. Journal of e-Biomedicine. 2016;4(1):2-6. Khan A, Tahir A, SU R, et al. Neuroprotective Effect of Quercetin Against the Detrimental Effects of LPS in the Adult Mouse Brain. Frontiers in Pharmacology. 2018;9:1-59. Muhammad Nizar. Probiotic Administration of Gingiva Lymphocyte Cells Count of Wistar Rats Induced by Lipopolysaccharides. Jember: Faculty of Dentistry, University of Jember. 2012. Hermida Md ER, de Melo CVB, Lima I dos S, Oliveira GG de S, dos-Santos WLC. Histological Disorganization of Spleen Compartments and Severe Visceral Leishmaniasis. Frontiers in Cellular and Infection Microbiology. 2018;8. doi:10.3389/fcimb.2018.00394 Maleki SJ, Crespo JF, Cabanillas B. Anti-inflammatory Effects of Flavonoids. Food Chemistry. 2019;299(July). Istanti NW, Nabila RA, Listyawati S. Nutritional Content of Black Rice (Oryza Sativa L.) Resulting from Breeding Plants with Gamma Rays of 60Co. Proceedings of Meetings and Scientific Presentations of Basic Research on Nuclear Science and Technology. Published online 2018:295-298. Maharni M. Potential of White Rice, Black Rice, and Brown Rice as Antioxidants and Inhibitors of Tyrosinase. Thesis of Bogor Agricultural University. Published online 2015:1-31. Zahroh F, Agustini R. Determination of the Total Anthocyanin Content of Black Rice Yeast Using the Differential pH Method. Journal of Chemistry of Neger University Surabaya. 2021;10(2):200-208. Arifa AH, Shamsir E, Budijanto S. Physicochemical Characterization of Black Rice (Oryza Sativa L.) from West Java, Indonesia. agriTECH. 2021;41(1):15. doi:10.22146/agritech.53307 Durga M, Nathiya S, Devasena T. Immunomodulatory and Antioxidant Actions of Dietary Flavonoids. International Journal of Pharmacy and Pharmaceutical Sciences. 2014;6(2):50-56. Tungmunnithum D, Thongboonyou A, Pholboon A, Yangsabai A. Flavonoids and Other Phenolic Compounds from Medicinal Plants for Pharmaceutical and Medical Aspects: An Overview. Medicines. 2018;5(3):93. Yu GJ, Choi IW, Kim GY, Kim BW, Park C, Hong SH. Anti-inflammatory Potential of Saponins Derived from Cultured Wild Ginseng Roots in Lipopolysaccharide-Stimulated RAW 264.7 Macrophages. International Journal of Molecular Medicine. 2015;35(6):1690-1698. Ahn S, Siddiqi MH, Noh HY, Kim YJ, Jin CG, Yang DC. Anti-inflammatory Activity of Ginsenosides in LPS-Stimulated RAW 264.7 Cells. Science Bulletin. 2015;60(8):773-784. Yang M, Koo S, Song W, Chun O. Food Matrix Affecting Anthocyanin Bioavailability: A Review. Current Medicinal Chemistry. 2011;18:291-300.